The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.bbrep.2021.100963
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-derived advanced glycation end-products having pyrrolopyridinium-based crosslinks

Abstract: Reducing sugars and reactive aldehydes, such as glyceraldehyde, non-enzymatically react with amino or guanidino groups of proteins to form advanced glycation end-products (AGEs) by the Maillard reaction that involves Schiff base formation followed by Amadori rearrangement. AGEs are found relatively in abundance in the human eye and to accumulate at a higher rate in diseases that impair vision such as cataract, diabetic retinopathy or age-related macular degeneration. We identified two novel AGEs of pyrrolopyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To date, the following GA-AGE structures have been detected: triosidines [41], GLAP [42], PPGs [43], MG-H1 [44], and ArgP [45] (Figures 1 and 2). Trihydroxy-triosidine, GLAP, and PPGs were identified in the Lys residues and MG-H1 and ArgP in the Arg residues of proteins.…”
Section: Structures Of Ga-agesmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the following GA-AGE structures have been detected: triosidines [41], GLAP [42], PPGs [43], MG-H1 [44], and ArgP [45] (Figures 1 and 2). Trihydroxy-triosidine, GLAP, and PPGs were identified in the Lys residues and MG-H1 and ArgP in the Arg residues of proteins.…”
Section: Structures Of Ga-agesmentioning
confidence: 99%
“…The pyridinium-type AGEs trihydroxy-triosidine and GLAP have been identified as GA-AGEs; however, their pathological effects are yet to be clarified. The Maillard reaction between N α -acetyl-L-Lys and GA was recently examined under physiological conditions and the main products identified were PPG1 and PPG2, which are fluorescent AGEs in which pyrrolopyridine ring structures cross-link two Lys molecules [43]. Based on these findings, a mechanism was proposed for the generation of PPG1 and PPG2 in vitro via a unique reaction to expand the skeleton as an alternative to the typical route for the formation of Schiff bases.…”
Section: Ppgsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study revealed that argpyrimidine and MG-H1 were generated from glyceraldehyde in PANC-1 and HPDE cells. Finally, other structures of GA-AGEs (unidentified in the cell) [1,110,111] could be included in the modification data, identified, and quantified.…”
Section: Comparison With Maldi-ms and Lc-esi-msmentioning
confidence: 99%